Philippine Astronomical Institute and Observatory Park - Santos, Angelo D.; Bo-ot, Ma. Luis (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
The design objective of this thesis is to develop a centralized institutional body that would provide the necessary focal point for the establishment of a cohesive learning program that would expand the knowledge for space sciences. The design problem is how to allow said project to become economically and functionally self-sustaining –through introduction of an income generating component – a commercial function would allow such to be resolved. Integrating educational and research systems to the complex also enable functional independence, increasing overall efficiency.
The central learning institute, a research observatory building, and a dormitory would constitute to the primary function of the development thus would compromise the ‘main complex’, and the commercial building – with a different user set would be located on a lower elevation. Site maximization through trail parks and bike paths and complete vehicular traffic segregation would be conducive to the overall experience intended. Locations of the infrastructures are dictated in accordance and in relation to the Observatory.
With the foundation of a centralized and integrated astronomical facility, it would act as a stepping stone in developing the public’s interest and overall learning in the field of science.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Philippine Astronomical Institute; Research facilities